Experience of instantaneous transaction coronary bypass surgery with carotid endarterectomy - B.M. Todurov; G.I. Kovtun; A.I. Matvijchuk; О.М. Postupalsky; А.О. Shpachuk; S.O. Sheludko; O.V. Revenko; O.A. Loskutov; M.A. Taranov (Кардіохірургія та інтервенційна кардіологія)
This article describes a case of successful revascularization under artificial circulation simultaneously with carotid endarterectomy. Based on experience (89 cases with zero lethality and no central nervous system complications), it is recommended to use this treatment approach in patients with atherosclerosis of coronary and brachiocephalic arteries. The method provides good outcomes, ensures rapid rehabilitation without neurological symptoms.